Development, implementation, and evaluation of a rapid response system at a Nigerian teaching hospital, a novel idea in sub-Saharan Africa - Promise Ariyo; Seung W. Lee; Asad Latif; Chinyere Egbuta; Vinciya Pandian; Olufemi Bankole; Ibironke Desalu; John Sampson; Bradford Winters (Frontiers in Medicine, 2025)
AimLittle is known about the incidence of clinical deterioration and cardiopulmonary arrest (CPA) on general hospital units in low-and middle-income countries (LMICs) or how rapid response systems (RRSs) might impact these events. Implementation of RRSs in high-income countries has been shown to reduce the incidence of CPA and mortality. The aim of this study was to determine whether implementation of an RRS is feasible in an LMIC medical center.MethodsWe developed and implemented an RRS in a large academic medical center in Lagos, Nigeria, in three phases: (1) Needs assessment and stakeholder engagement, (2) Infrastructure setup and education, and (3) Implementation and data collection. We collected data on incidence of rapid response events, attendance ratio and time of arrival of the designated clinical staff, triggers for the rapid response calls and common interventions at the events.ResultsOver the 7 months study period, 997 patients were admitted to the intervention-eligible units, and 95 RRS events occurred in 55 patients. In 11 RRS activations (11.6%), no rapid response team member responded. Anesthesia residents attended 73.7% of the events, and anesthesia techs and nurses attended roughly 38% each. Internal medicine residents responded to 13.7% of RRS activations. The average time to arrival was 13 min. The most common trigger was altered mental status, followed by hypoxia and hypotension. Seventy-six percent of patients survived their initial RRS activation, and 83% died while in hospital. Common interventions were vasopressor use, oxygen supplementation, and intravenous fluid administration. No patient was transferred to the designated intensive care unit after an RRS activation owing to lack of beds. Six patients were transferred to the makeshift ICU, all of which required vasopressor support.ConclusionWhile barriers remain, the development and implementation of an RRS program in an LMIC medical center is feasible.